Small-molecule Inhibitors of Fibroblast Growth Factor Receptor (FGFR) Tyrosine Kinases (TK) - Manetti, F.; Botta, M. (Current Pharmaceutical Design, 2003)
Fibroblast growth factor receptors (FGFR) are members of a family of polypeptides synthesized by a variety of cell types during the processes of embryonic development and in adult tissues. FGFR have been detected in normal and malignant cells and are involved in biological events that include mitogenic and angiogenic activity with a consequent crucial role in cell differentiation and development. To activate signal transduction pathways, FGFR are coupled to fibroblast growth factors (FGF) and heparan sulfate (HS) proteoglycans to form a biologically fundamental ternary complex. Based on these considerations, a variety of inhibitors able to block the signaling cascade through a direct interaction with FGFR have been designed and investigated for their biological properties related to antiangiogenesis and antitumor activity. The purpose of this review is to focus on synthetic chemical approaches aimed at blocking tyrosine kinase (TK) receptors, members of the FGFR family. In particular, a literature survey aimed at summarizing on the structural properties that a compound should possess to show affinity toward FGFR is presented, and structure-activity relationships (SAR) on FGFR inhibitors are delined.
Keywords: Growth Factor Receptor